Exploring Technical Vocational Teacher Education: Inputs To Curriculum Model Development - I. Moreno, Nilmar; Z. Callueng, Romelyn; P. Portez, Apollo (Journal of Technical Education and Training, 2025)
The global demand for skilled workers, particularly in digital sectors, is projected to increase significantly, with an estimated 92 million digital jobs expected by 2030, according to the World Economic Forum. This trend presents a unique opportunity for countries like the Philippines to enhance their Technical and Vocational Education and Training (TVET) systems to meet evolving global labor market needs. Hence, this study endeavored the development of a comprehensive, research-based curriculum model for the Bachelor of Technical-Vocational Teacher Education (BTVTEd) program in the Philippines. Using an exploratory sequential mixed-methods approach, the research examined current challenges, and the extent of knowledge, experiences, and practices within the BTVTEd curriculum by gathering insights from experts in universities across the country. The findings reveal that the main challenges identified by respondents are related to curriculum and program design, particularly in adapting to industry demands. However, issues related to resources and facilities were also highlighted as central concerns. The study further underscores the need for the inclusion of emerging key courses, such as research, innovation, sustainability, and regulatory frameworks, alongside strengthening core areas like pedagogy, instructional design, and personal and professional development. Additionally, the study identified prominent factors, practices and strategies used to improve the BTVTEd program. Based on these findings, a new curriculum model is proposed, aimed at strengthening the current technical education program. The study suggests further exploration on how universities balance the use of quality assurance practices in curriculum delivery. The results provide valuable insights for the continued development of technical vocational teacher education in the Philippines through comprehensive quality assurance.